Undead ahead - Kloepfer, John.; Wolfhard, Steve (New York : Harper, 2011)
While trying to survive after zombies take over Phoenix, Arizona, Zack, Rice, and Madison discover a zombie antidote and embark on a mission to save the nation from the undead scourge.
Includes excerpt of Sludgment Day.
Accelerated Reader AR
Keywords: Zombies -- Fiction; Survival -- Fiction; Phoenix (Ariz.) -- Fiction; Humorous stories